TECHNOLOGY SELF-EFFICACY AND DIGITAL LITERACY AMONG ODL STUDENTS: THE MODERATING ROLE OF GENDER - Itasanmi, Sunday Abidemi; Ajani, Ayodele Oluwatoyin (International Journal of Innovative Technologies in Social Science, 2023)
This study investigated Open Distance Learning (ODL) students’ technology self-efficacy and digital literacy levels and how the relationship between their technology self-efficacy and digital literacy is moderated by gender. The study adopted a quantitative survey research approach and data was collected from 522 students from a selected ODL institution in Nigeria using an online survey. A structured questionnaire consisting of 3 domains namely, demographic, technology self-efficacy and digital literacy were used as a data collection instrument for the study. Data generated from the study were analysed using descriptive statistics of percentages, frequency count, mean and standard deviation while correlation and factor analyses were performed to estimate the model’s consistency and construct validity. The moderating role of gender was done using the process macro (Model 1) developed by Hayes, (2018). Results revealed amongst others that ODL students’ technology self-efficacy is very high and their digital literacy rate is high. Also, technology self-efficacy was shown to exhibit a substantial positive influence on digital literacy among the students. However, the results indicated that gender played an insignificant moderating role in the relationship between technology self-efficacy and digital literacy. Based on the results, it was recommended that efforts at increasing digitization in ODL delivery in Nigeria should take into consideration these factors. Also, policy actions aimed at engaging ODL learners in more technologically sophisticated learning platforms must be anchored on students’ belief in their ability to use the learning platforms to achieve their desired learning outcomes irrespective of their gender.